DOES THE TENDINOPATHIC PATELLAR TENDON NORMALISE, ACCORDING TO ULTRASOUND FINDINGS, AFTER TREATMENT WITH SCLEROSING INJECTIONS OR ARTHROSCOPIC SHAVING? A LONG TERM FOLLOW-UP (3–5 YEARS). Issue 9 (10th May 2013) - Sunding, K; Willberg, L; Niklasson, U; Werner, S
Abstract : Introduction: Treatment of patellar tendinopathy/jumper's knee with ultrasound-guided sclerosing injections and arthroscopic shaving has shown good clinical results, but patients treated with the one-stage procedure arthroscopic shaving had a faster return to full activity, less pain and were more satisfied with the treatment result at follow-up approximately 1 year after end of treatment.1 There are studies suggesting that tendon structure in a tendinotic, chronic painful tendon does not sonographically normalise after successful treatment. However those results are based on a relatively short term follow up. Methods: We have evaluated patellar tendons according to a routine ultrasound examination protocol for chronic painful patellar tendons/proximal patellar tendinopathy, 3 to 5 years after treatment with sclerosing injections (n=19) or arthroscopic shaving (n=25). Tendon thickness was measured and tendon structure and the amount of neovascularization was evaluated and scored, to be compared with corresponding values at baseline and at the 1 year follow-up. Self-reported pain during rest and patellar tendon loading activity, and patient satisfaction with the result of the treatment was registered on a visual analogue scale (VAS). Results: At the 3–5 years follow-up, preliminary results showed that tendon structure seemed to improve, and the neovascularisation was reduced, in both groups. There was a trend towards a decrease in antero-posterior thickness of the proximal part of the patellar tendon in patients treated with arthroscopic shaving, but not for tendons treated with sclerosing injections. There were no differences in VAS score at rest and during activity between the two treatment groups or in VAS score for satisfaction with treatment. Discussion: Treatment of patellar tendinopathy/jumper's knee with ultrasound and colour Doppler-guided sclerosing injections and arthroscopic shaving showed remaining good clinical results after 3–5 years for both methods. Treatment with sclerosing injections requires multiple injections with 6–8 weeks in between, but in the 3–5 years perspective seems to reach the same result in terms of ultrasound findings and self-reported pain (VAS) as treatment with the one-stage procedure arthroscopic shaving. This is in contrast to the results at 1 year follow-up where the surgical method showed better results in all evaluated variables. One remaining difference between the two treatments was that only the surgical method showed a decrease in antero-posterior thickness. In fact tendon thickness in the group treated with sclerosing injections were increased at the 1 year follow-up, while now 3–5 years after treatment the thickness seems to be back at the same level as at baseline, before treatment.